Personal and Gender Features of Value-Motivational Structure of Innovativeness - O B Mikhailova (Peoples' Friendship University of Russia (RUDN University), 2014)
The article provides new approaches to analyzing and studying value motivational aspects of personal activity that predetermine innovative activity and submits the analysis of a comparative empirical research of value motivational characteristics in students with different levels of innovativeness. On the basis of the detailed description of the strategy of the research the paper presents new significant characteristics of the value motivational sphere of young men and girls.